The Standard of Care for Immune Thrombotic Thrombocytopenic Purpura Today - Zheng, X. Long (J Thromb Haemost, 2021)
Targeted therapy of immune thrombotic thrombocytopenic purpura (iTTP) requires acurate and prompt diagnosis and differentiation from complement-mediated hemolytic uremic syndrome and other causes of thrombotic microangiopathy. ADAMTS13 evaluation (activity and inhibitors or anti-ADAMTS13 IgG) is the key for diagnosis and further management of patients with suspected iTTP during acute episode and in clinical response or remission. Clinical trial results and real-world data have demonstrated the efficacy and safety of the triple therapy consisting of therapeutic plasma exchange, caplacizumab, and immunosuppressives (e.g. corticosteroids and rituximab) for acute iTTP. Such a therapeutic strategy has significantly accelerated the normalization of platelet counts, decreased the length of stays in the intensive care unit and the hospital, but most importantly reduced the mortality rate. The present review highlights some of the important advancements for the diagnosis and management of iTTP and propose the triple therapy as the standard of care for acute iTTP today.